A mitogen-activated protein kinase NtMPK4 activated by SIPKK is required for jasmonic acid signaling and involved in ozone tolerance via stomatal movement in tobacco [Nicotiana] - Gomi, K.(National Inst. of Agrobiological Sciences, Tsukuba, Ibaraki (Japan)); Ogawa, D; Katou, S; Kamada, H; Nakajima, N; Saji, H; Soyano, T; Sasabe, M; Machida, Y; Mitsuhara, I; Ohashi, Y; Seo, S (Plant and cell physiology, 2005)
The mitogen-activated protein kinase (MAPK) cascade is involved in responses to biotic and abiotic stress in plants. In this study, we isolated a new MAPK, NtMPK4, which is a tobacco homolog of Arabidopsis MPK4 (AtMPK4). NtMPK4 was activated by wounding along with two other wound-responsive tobacco MAPKs, WIPK and SIPK. We found that NtMPK4 was activated by salicylic acid-induced protein kinase kinase (SIPKK), which has been isolated as an SIPK-interacting MAPK kinase. In NtMPK4 activity-suppressed tobacco, wound-induced expression of jasmonic acid (JA)-responsive genes was inhibited. NtMPK4-silenced plants showed enhanced sensitivity to ozone. Inversely, transgenic tobacco plants, in which SIPKK or the constitutively active type SIPKKEE was overexpressed, exhibited greater responsiveness to wounding with enhanced resistance to ozone. We further found that NtMPK4 was expressed preferentially in epidermis, and the enhanced sensitivity to ozone in NtMPK4-silenced plants was caused by an abnormal regulation of stomatal closure in an ABA-independent manner. These results suggest that NtMPK4 is involved in JA signaling and in stomatal movement.